2005
DOI: 10.1111/j.1542-474x.2005.00634.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetocardiography Predicts Coronary Artery Disease in Patients with Acute Chest Pain

Abstract: For the prediction of CAD in patients presenting with acute chest pain and without ST-segment elevation, an admission MCG test was superior to an admission ECG, ECHO, and troponin-I. The results of the study, however, are applicable only to a highly selected population comprising patients in whom immediate coronary angiography can be performed based on their clinical course in the hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
85
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(86 citation statements)
references
References 14 publications
1
85
0
Order By: Relevance
“…Using our method, the presence of CAD is determined by comparing the probability, which was calculated from the prior knowledge on the probability distribution of the MCG parameters depending on the presence of CAD. In this way we obtained better diagnostic accuracy than the previous studies, [11][12][13][14] showing that the proposed method is more effective than the conventional binary decision method. This wMAP method was tested with a small population (86 CAD patients, 59 minimal CAD patients, 66 healthy volunteers) and was applied to all patients to confirm the validity in a relatively large population.…”
Section: Discussionmentioning
confidence: 37%
See 1 more Smart Citation
“…Using our method, the presence of CAD is determined by comparing the probability, which was calculated from the prior knowledge on the probability distribution of the MCG parameters depending on the presence of CAD. In this way we obtained better diagnostic accuracy than the previous studies, [11][12][13][14] showing that the proposed method is more effective than the conventional binary decision method. This wMAP method was tested with a small population (86 CAD patients, 59 minimal CAD patients, 66 healthy volunteers) and was applied to all patients to confirm the validity in a relatively large population.…”
Section: Discussionmentioning
confidence: 37%
“…12 A sensitivity and a specificity of >90% were recently reported in patients admitted to the intensive care unit, using four variables derived during ST-T interval. 13 But in that study 63 out of 264 datasets had to be excluded due to insufficient signal-to-noise ratio, because they measured MCG with a 9-channel system in an unshielded environment. In contrast, another group reported a sensitivity of 76.4% and a specificity of 74.3% in a similar situation.…”
Section: Non-invasive Detection Of Cad By Mcgmentioning
confidence: 99%
“…Computerized diagnosis of the isomagnetic map has also been investigated. 19 Park et al 20 found that analysis of isomagnetic maps obtained from admission MCG is superior to admission ECG, echocardiography and troponin-I levels in predicting coronary artery disease in patients with chest pain but without ST-segment elevation.…”
Section: Discussionmentioning
confidence: 99%
“…Multichannel MCG mapping measures the magnetic fields (MF) generated by cardiac activation currents, with minimal distortion due to the shape and conductivity of the lungs and torso (20, 28). The advantages of contactless MCG mapping are as follows: 1) the ability to study conscious animals without movement artifacts (65), 2) the potential to provide diagnostic information not revealed by ECG (1,29,36,37,41,43,44,51,54,62,64,69,71,74,75), 3) the fixed-sensors geometry (42), which minimizes errors in localization of intracardiac sources (30) and three-dimensional electroanatomic imaging of arrhythmogenic phenomena (77), and 4) the localization of VR heterogeneities associated with areas of myocardial injury (50).A major problem with MCG mapping of small hearts might be an unfavorable signal-to-noise ratio (S/N), because the cardiac sources are very weak. For this reason, most experimental MCG studies of small animal hearts have been performed in magnetically shielded rooms (4,22,23,65,72).…”
mentioning
confidence: 99%